Utility of Filter Paper for Preserving Insects, Bacteria, and Host Reservoir DNA for Molecular Testing - F Karimian; MM Sedaghat; MA Oshaghi; F Mohtarami; A Sanei Dehkordi; M Koosha; S Akbari; SS Hashemi-Aghdam (Tehran University of Medical Sciences, 2011)
Background: Appropriate methodology for storage biological materials, extraction of DNA, and proper DNA preservation is vital for studies involving genetic analysis of insects, bacteria, and reservoir hosts as well as for molecular diagnostics of pathogens carried by vectors and reservoirs. Here we tried to evaluate the utility of a simple filter paper-based for storage of insects, bacteria, rodent, and human DNAs using PCR assays. Methods: Total body or haemolymph of individual mosquitoes, sand flies or cockroaches squashed or placed on the paper respectively. Extracted DNA of five different bacteria species as well as blood specimens of human and great gerbil Rhombomys opimus was pipetted directly onto filter paper. The papers were stored in room temperature up to 12 months during 2009 until 2011. At monthly intervals, PCR was conducted using a 1-mm disk from the DNA impregnated filter paper as target DNA. PCR amplification was performed against different target genes of the organisms including the ITS2-rDNA of mosquitoes, mtDNA-COI of the sand flies and cockroaches, 16SrRNA gene of the bacteria, and the mtDNA-CytB of the vertebrates. Results: Successful PCR amplification was observed for all of the specimens regardless of the loci, taxon, or time of storage. The PCR amplification were ranged from 462 to 1500 bp and worked well for the specified target gene/s. Time of storage did not affect the amplification up to one year. Conclusion: The filter paper method is a simple and economical way to store, to preserve, and to distribute DNA samples for PCR analysis.